Nutrition and Its Relationship to Physical Appearance in Children with Cancer - Happy Indri Hapsari; Rita Benya Adriani; Dwi Sulistyowati (Indonesian Journal of Global Health Research, 2025)
Cancer treatment experienced by children and adolescents has a wide range of impacts, including nutritional status. Nutritional status changes the shape of children and adolescents with cancer. The purpose of this study was to analyze the relationship between malnutrition and the physical appearance of children with cancer. The design of this study was cross-sectional, the sampling technique used was purposive sampling, with cancer children undergoing active treatment who were school-aged and adolescents. There are 47 respondents. Multiple regression is a statistical analysis in this study. Data were collected directly at the hospital after obtaining ethical approval and permission from the hospital and the patient's parents/guardians, using physical measurements (LLA) and questionnaires (SPPC), as well as demographic data. Predicted factors of physical appearance (R2 = 0.36, p = 0.00) were sex (β = -0.17, p = 0.27), age (β = 0.02, p = 0.48), cancer type (β = 0.24, p = 0.51), and nutritional status (β = 0.12, p = 0.00). Being female, older, having solid mass cancer, and having a higher body mass index will affect the physical appearance of a child with cancer. Children with cancer are particularly susceptible to nutritional problems, both undernourished and overnourished, which directly affect their physical appearance. These changes, such as hair loss, weight changes, and skin color, create significant psychological distress on children and adolescents, especially due to concerns about social acceptance. Studies show that good nutritional status is positively correlated with better physical appearance, underscoring the importance of comprehensive nutritional interventions as an essential part of childhood cancer care. Nutritional status is the most significant predictor of the physical appearance of children with cancer, where better nutrition is directly correlated with better physical appearance. Cancer is more common in boys and blood cancer is most common, physical changes due to treatment greatly affect psychological well-being, especially in adolescent girls who feel greater pressure related to body image.